elites - Grigoryeva, Elena (project baikal, 2016)
Who are the elite? Those who are called elite today, Will be forgotten next day. Those who are today killed or brought low, Will be the elite tomorrow. January 15, 2016 is Mandelstam’s 125th anniversary Since classical antiquity many minds have been concerned about the elites. At first glance, it is obvious that elites are the best and chosen people who have power, wealth and a decisive impact on the society. However, any attempt to clarify the definition leads to discrepancy. Gaetano Mosca asserts bitterly that the elites are always self-appointed. Those who have power and wealth will claim themselves elite. On the contrary, Vilfredo Pareto says about the superiority of elites over common people by virtue of their skills, will and energy. The argument continues. This subject has so many sides that we do not claim its complete coverage within one issue. It is quite telling that this subject aroused keen interest among regular authors of PB, and they launched a discussion in the Internet space (120). Though this genre is new for our journal, it has immediately involved three countries and five points on the map. Whatever definition we give to elites, it is doubtless that a lot of things depend on their composition, quality, will and goals. Will it be war or peace, and what kind of war or peace will it be? Will justice finally reign, or will iniquities and outrages go on? Will the crumbling economies bring us to hunger or to a new round of prosperity? Which elite – financial, power or professional – has the greatest impact on the condition of our cities and city quarters? Is the architectural style formed naturally, as a respond to the society’s requirements? Does it reflect the condition of technologies, or is it imposed authoritatively from above? As usual, there are a lot of questions, much more than the answers. The questions are urgent and uneasy. Well, the greater the journal’s chances to become interesting, comprehensive and elite, in a good sense.